2015
DOI: 10.1038/nmeth.3473
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling CRISPR-Cas9 genome engineering parameters via a library-on-library approach

Abstract: We develop an in vivo library-on-library methodology to simultaneously assess single guide RNA (sgRNA) activity across ~1,400 genomic loci. Assaying across multiple human cell types, end-processing enzymes, and two Cas9 orthologs, we unravel underlying nucleotide sequence and epigenetic parameters. Our results enable improved design of reagents, shed light on mechanisms of genome targeting, and provide a generalizable framework to study nucleic acid-nucleic acid interactions and biochemistry in high throughput. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
403
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(417 citation statements)
references
References 29 publications
11
403
2
1
Order By: Relevance
“…This observation contrasts with early reports indicating that this ortholog was mildly active 7,34 . This led us to investigate whether we could further boost its activity.…”
Section: Identification Of An Sgrna Architecture Directing Robust Dnacontrasting
confidence: 99%
“…This observation contrasts with early reports indicating that this ortholog was mildly active 7,34 . This led us to investigate whether we could further boost its activity.…”
Section: Identification Of An Sgrna Architecture Directing Robust Dnacontrasting
confidence: 99%
“…For future improvements in Cas9 proteins, we suggest that one should focus on rapid rejection of such off targets. Our observations may also further inform the design of the guide-RNA and the DNA targets with minimal off-target effects [57][58][59][60][61][62][63][64][65][66][67][68] .…”
Section: Discussionmentioning
confidence: 80%
“…A single study that combined Trex2 with Cas9 for gene editing in human cells reported a similar 2.5-fold increase in mutagenesis (Chari et al, 2015). When Trex2 was used in combination with TALENs, a 3-to 4-fold enhancement was observed (Certo et al, 2012;Luo et al, 2015), whereas a 25-fold increase was achieved when a meganuclease was used as the DSB-inducing agent (Certo et al, 2012).…”
Section: Discussionmentioning
confidence: 92%